Improving SNR Of Radar Signal Using Wavelet De-Noising Scheme (International Journal of Engineering and Computer Science, 2015)
The purpose of Radar signal processing is to extract the desired data from radar signals. The accuracy of data available from radar is limited by thermal noise introduced by the radar receiver, echoes from targets of no interest (known as clutter) and extremely generated interference. As a result radar signal processing is also used to enhance signals and to suppress clutter and externally generated signals. In this paper wavelet denoising is used to improve SNR.